Improving Teachers’ STEM Competence: Impact of A Collaborative Professional Development Workshop - Ekawati, Rooselyna; Indana, Sifak; Wasis, Wasis; Artiono, Rudianto; Novita, Dian; Trimulyono, Guntur; Mahdiannur, Muhammad Arif (Jurnal Karya Abdi Masyarakat, 2025)
The Science, Technology, Engineering, and Mathematics (STEM) approach to learning plays an important role in improving teacher competency, learning innovation, and technology use skills. However, the results of an initial survey at Sekolah Indonesia Makkah showed that 44.12% of teachers faced challenges in the form of a lack of training and understanding related to STEM integration. This study involved 34 teachers and aimed to improve their ability to implement STEM-based learning through the Collaborative Professional Development (CPD) approach. The results showed that teachers who participated in CPD activities experienced a significant increase in their understanding and readiness to implement STEM. In addition, teachers began to realize the benefits of STEM learning in developing students’ affective, cognitive, and psychomotor aspects, as well as its potential as a means of career guidance. As many as 52.94% of teachers stated that they strongly believed that STEM was important to implement, and 58.82% considered the CPD program to be continued. This study recommends that CPD training be carried out continuously with more applicable and contextual materials. Strengthening collaboration between teachers and the integration of STEM-based curriculum is also needed to support the sustainability and effectiveness of the program in the long term.